2017
DOI: 10.3847/1538-4357/aa5b9d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Overshooting of the Convective Core on Main-sequence Turnoffs of Young- and Intermediate-age Star Clusters

Abstract: Recent investigations have shown that the extended main-sequence turnoffs (eMSTOs) are a common feature of intermediate-age star clusters in the Magellanic Clouds. The eMSTOs are also found in the color-magnitude diagram (CMD) of young-age star clusters. The origin of the eMSTOs is still an open question. Moreover, asteroseismology shows that the value of the overshooting parameter δ ov of the convective core is not fixed for the stars with an approximatelly equal mass. Thus the MSTO of star clusters may be af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…An overlooked role possibly related to the presence of eMSTO regions is convective overshooting. Yang & Tian (2017) calculated the impact of convective overshooting on the MSTO of clusters as young as 100 Myr. They found that adoption of varying overshooting parameters(δ ov ) for individual stars-with δ ov varying from 0.0 to 0.7-can potentially explain the observed eMSTOs in young and intermediate-age clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overlooked role possibly related to the presence of eMSTO regions is convective overshooting. Yang & Tian (2017) calculated the impact of convective overshooting on the MSTO of clusters as young as 100 Myr. They found that adoption of varying overshooting parameters(δ ov ) for individual stars-with δ ov varying from 0.0 to 0.7-can potentially explain the observed eMSTOs in young and intermediate-age clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Such a nitrogen abundance dispersion cannot be produced by any combination of rotating models with moderate overshooting, δ ov = 0.2, and non-rotating models. This may then be used to differentiate convective core overshooting models from rotation models (Yang & Tian 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As such, we investigate if the asteroseismically calibrated mixing mechanisms discussed above, and particularly their consequence in terms of increased core mass, play a role in the formation of the eMSTO of young open clusters. Yang & Tian (2017) already considered the case of allowing for different levels of convective penetration as the mechanism for CBM for non-rotating stellar models of a coeval population and showed that this can explain the eMSTO to some extent. We generalise this approach to investigate to what level the mixing profiles calibrated by asteroseismology of stars with a convective core can explain the eMSTOs of young clusters.…”
Section: Introductionmentioning
confidence: 99%
“…These areas naturally form an extended TAMS region. Unlike Yang & Tian (2017), who only considered penetrative convection with un-calibrated large values of the penetration distance up to 0.7 times the local pressure scale height, we consider the general case of both CBM and REM and limit the overall amount of CBM and REM to measured levels calibrated by asteroseismology of intermediate-and high-mass field stars as achieved by the MfA studies. We fit isochrone-clouds to CMDs of two prototypical clusters with observed eMSTOs to illustrate the capacity and limitations of isochrone clouds in explaining this observed phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple scenarios have been proposed to explain the observational results, including an extended star formation history (Goudfrooij et al 2011), variable stars (Salinas et al 2016), stellar rotation, and convective overshooting (Yang & Tian 2017). Thus far, the stellar rotation interpretation is most favored by a range of observations, including the 2 W. Sun et al…”
Section: Introductionmentioning
confidence: 99%